"'No Tough Guys Here?': Hybrid Masculinity in a Boxing Gym". (April 2021) - Rabii, Watoii
In this article, I explore manifest and latent discourses about masculinity in a predominantly white, middle class boxing gym. In this gym, the owner and coaches promote a discourse that emphasizes love, bridgework, and sparring with care. This discourse is part of the gym's white-collar boxing culture. A key part of this discourse is distancing themselves from other gyms, claiming they promote a violent masculinity. While on the surface the gym criticizes certain ideals and practices associated with American hegemonic masculinity, it still reproduces discourses, norms, and practices associated with it. Employees use a latent discourse that constructs a hybrid masculinity. I argue that employees and members construct a hybrid masculinity by perpetuating ideals and practices associated with American hegemonic masculinity.